Anime Trend as An Advert Genre in Indonesian Youtube - Novi Andari; Adeline Grace M Litaay (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Anime is a loanword from English 'animation' which is absorbed into Japanese. The rise of anime fans among teenagers in recent years has led companies to increase sales by using product marketing in the form of anime-style advertising media on television. This scientific articles aim to find out about anime trends in Indonesia and what their impact is on the advertising media for a product in Indonesia. This study was conducted by applying the qualitative method of which the discussion was presented descriptively. The data of this study were obtained by using observation and note taking technique. The results of this study indicate that there is an increase in the number of viewers on anime-style advertisements compared to non-anime-style ads.